Intrinsic carrier mobility extraction based on a new quasi-analytical model for graphene field-effect transistors. (22nd September 2016) - Wang, Shaoqing; Jin, Zhi; Muhammad, Asif; Peng, Songang; Huang, Xinnan; Zhang, Dayong; Shi, Jingyuan
Abstract: The most common method of mobility extraction for graphene field-effect transistors is proposed by Kim. Kim's method assumes a constant mobility independent of carrier density and gets the mobility by fitting the transfer curves. However, carrier mobility changes with the carrier density, leading to the inaccuracy of Kim's method. In our paper, a new and more accurate method is proposed to extract mobility by fitting the output curves at a constant gate voltage. The output curves are fitted using several kinds of current–voltage models. Besides the models in the literature, we present a modified model, which takes into account not only the quantum capacitance, contact resistance, but also a modified drift velocity-field relationship. Comparing with the other models, this new model can fit better with our experimental data. The dependence of carrier intrinsic mobility on carrier density is obtained based on this model.